Workers survived from commuting road crashes: who are they? - Sahak, Nurrul Hafeezah; K.C. Mani, Kulanthayan; Hamedon, Titi Rahmawati; Rampal, Krishna Gopal; Vythialingam, Kathirkamanathan (Human Resource Management Academic Research Society, 2020)
Background: Commuting road crashes are road traffic crashes that involve workers while travelling in the course of work. The more worker travels, the higher the probability of the occurrence of commuting road crashes. The aim of this study was to determine baseline sociodemographic, employment and injury and characteristics of injured workers who survived from commuting road crash. Methods: Eligible 200 workers who were involved in commuting road crash were identified and invited to be part of this study. Sociodemographic, employment and injury-related questions were distributed to identified and consented injured workers. Results: Majority (79.5%) of the respondents were aged 25 years old or older, male (86.0%), married or divorced (63.5%), and attained secondary and below education level (66.0%). Most of the injured workers consisted of blue-collar workers (69%), had fracture injury (93.0%), and had injury to their lower limbs (48.5%). A higher percentage (63.5%) of injured workers had returned to work compared to those who were still not working (36.5%) after involved in commuting road crash. Conclusion: Commuting road crashes are common to blue collar workers as they are more prone to use motorcycles to commute due to cheaper price compare to other type of transportation such as car.